A Case of Large Perianal Mucinous Adenocarcinoma Arising from Recurrent Abscess and Complex Fistulae. (19th December 2020) - Azmi, Fahmi Pramaditto; Rahman, Nur Afdzillah Abdul; Mazlan, Luqman; Basiron, Normala; Imran, Farrah-Hani
Abstract : Mucinous adenocarcinoma of the perianal region is an oncologic rarity posing a diagnostic and therapeutic dilemma for treating oncologists. This is due to the low number of reported cases, compounded by the lack of definitive therapeutic guidelines. It accounts for 2% to 3% of all gastrointestinal malignancies and is historically known to arise from chronic anal fistulas and ischiorectal or perianal abscesses. We hereby report an interesting case of perianal mucinous adenocarcinoma in a 66-year-old male initially treated for a horseshoe abscess with complex fistulae. He presented with a 6-month history of a discharging growth in perianal region and painful defecation associated with occasional blood mixed stools. An incisional biopsy from the ulcer revealed mucinous adenocarcinoma. Contrast-enhanced computed tomography (CT) scan and magnetic resonance imaging (MRI) scan showed a localized perianal growth which involves the internal and external sphincter as well as suspicious involvement in the posterior aspect of the levator ani/puborectalis sling, which was further confirmed with colonoscopy (see figures). With no preset treatment protocol for this rare entity, he was managed with an abdominoperineal resection (APR) and vertical rectus abdominis myocutaneous flap (VRAM) tissue reconstruction. He had a turbulent postoperative period including intestinal obstruction secondary to internal herniation of bowel resulting in flap failure. The subsequent perineal wound was managed conservatively with advanced wound care and has since completely healed.